A Failed Response? The Humanities in Transition - Ekström, Anders (Academic Quarter | Akademisk kvarter, 2016)
This essay discusses the changing role of arts and humanities research and education in the context of continuing transitions in knowledge politics and society at large. It argues that a conflicted history of both expansion and marginalization has conditioned the humanities for reactive critique in ways that limits its influence. This calls for a rearticulation of the role of humanistic knowledge in a time when society’s most challenging transitions are connected by their cultural dimension, understood in its most basic sense of the influence on society of human action, communication, cultural routines and value formation. To scale-up the impact of the humanities, and sharpen its knowledge claims, a development towards integrative and plural forms of knowledge environments is suggested.